Histological and hemodynamic characterization of corpus luteum throughout the luteal phase in pregnant and non-pregnant buffalos in relation to nitric oxide levels based on its anatomical determination - Daghash, Samer M.; Yasin, Noha A. E.; Abdelnaby, Elshymaa A.; Emam, Ibrahim A.; Tolba, Ayman; Abouelela, Yara S. (Frontiers in Veterinary Science, 2022)
This study aimed to compare the complete growth and development of corpus luteum (CL) in domestic buffalos from day 5 until day 40 after ovulation either in pregnant or non-pregnant ones and whether luteal vascularity (LV) with progesterone (P4) and nitric oxide (NO) could determine luteal functionality or not. Pluriparous buffalos (Bubalus bubalis) were categorized into pregnant (n = 6), and non-pregnant (n = 9) after pregnancy check at day 25. Animals were subjected to ultrasound analysis to determine CL area (cm2) and LV. Blood sampling was performed following the Doppler examination. Ovarian tissue samples from non-pregnant buffalo genitalia (n = 18) and early pregnant buffalo genitalia (n = 3) were collected from great abattoirs. Luteal Doppler indices were lower in the pregnant group, while peak systolic velocity (PSV) was increased (P < 0.05) in the same pregnant females. Both P4 and NOMs were elevated (P < 0.05) in the pregnant group. There was a positive correlation (P < 0.01) between P4 and CL PSV. Based on our macroscopical examination, the CL of non-pregnant buffalos was classified into four stages. Histologically, stage I showed that CL was covered by a highly vascularized connective tissue (CT) capsule. It consisted of small and large lutein cells, whereas stage II was similar to stage I except for the presence of numerous fibroblast cells and vacuolated cells. Stage III was characterized by increasing the number of collagen fibers and the thickness of the blood vessels. Stage IV revealed thickening of the CT capsule and septae, regressed capillaries and arterioles in addition to shrunken degenerated lutein cells. CL of pregnant buffaloes revealed the same structure of CL at stage II. CL area was increased in the pregnant group. The collective data suggested that evaluation of the luteal artery could be extremely helpful to determine the potential benefits of coloured and pulsed Doppler in CL vascularization assessment in both luteal and early pregnancy phases.